2015
DOI: 10.1089/ten.tea.2014.0156
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Water-Soluble Chitin on Collagen Synthesis of Human Bone Marrow Stem Cells and Human Periodontal Ligament Stem Cells

Abstract: Human bone marrow stem cells (hBMSCs) represent a promising regenerative material because of their mutipotency, including their ability to regenerate collagenous soft tissues. We previously found that water-soluble chitin (WSC) enhances the ability of human periodontal ligament stem cells (hPDLSCs) to synthesize collagen tissue. The aim of this study was to determine the effects of WSC on hBMSCs and hPDLSCs for the collagen synthesis both in vitro and in vivo. hBMSCs and hPDLSCs were isolated and expanded with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…The expression of DSPP, a specific marker of odontogenic differentiation, indicated that the transgenic PDLSCs retained their odontogenic differentiation potential under osteoinductive conditions . Eph/ephrins are known to be involved in osteochondral differentiation of MSCs, and overexpression of ephrinB2 has been shown to enhance osteogenesis of human MSCs . The enhancement of mineralized matrix formation by PDLSCs overexpressing ephrinB2 required intimate cell contact to activate ephrinB2 interaction with EphB4 or EphB2, as reported previously for osteoblasts .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The expression of DSPP, a specific marker of odontogenic differentiation, indicated that the transgenic PDLSCs retained their odontogenic differentiation potential under osteoinductive conditions . Eph/ephrins are known to be involved in osteochondral differentiation of MSCs, and overexpression of ephrinB2 has been shown to enhance osteogenesis of human MSCs . The enhancement of mineralized matrix formation by PDLSCs overexpressing ephrinB2 required intimate cell contact to activate ephrinB2 interaction with EphB4 or EphB2, as reported previously for osteoblasts .…”
Section: Discussionsupporting
confidence: 79%
“…Treatment of PDLSCs with water‐soluble chitin increased insoluble collagen formation, which may generate more mature and stable collagen fibrils. By contrast, subjecting bone marrow‐derived MSCs to the same treatment significantly enhanced the formation of both soluble and insoluble collagen . Differences in the phenotypes and functionality of different MSC types will have a profound impact on tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh human BM was harvested from the VB adjacent to the degenerative IVD tissue in the same subject during orthopedic surgery (Naeun Hospital, Suwon, Korea), using the same protocol as in our previous studies 35,36 . The patients provided informed consent for their tissue to be used in accordance with guidelines approved by the IRB of the College of Dentistry at Yonsei University (IRB No.…”
Section: Methodsmentioning
confidence: 99%
“…Elastin damage may occur under the conditions of the excess mechanical and thermal forces that occur in several diseases, such as PFD. LOX is involved in the initiation of collagen synthesis and elastin cross-linkage, and it ensures that tropoelastin molecules remain highly crosslinked to one another, thus performing an indispensable role in the construction of connective tissue [29]. Yamamoto et al [30] reported that the elastin expression level in the uterus was closely associated with POP, and the gene and protein levels of elastin were significantly decreased in the POP group compared with the control group.…”
Section: Discussionmentioning
confidence: 99%